ANALISIS KESULITAN BELAJAR MAHASISWA PENDIDIKAN GURU MADRASAH IBTIDAIYAH PADA PEMBELAJARAN PAI - Nurjanah Nurjanah; Saprin Saprin; Rosdiana Rosdiana; Immawati Rivai (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine the form of learning difficulties and the factors that cause learningdifficulties for PGMI B students class 2017 in PAI learning courses at the Tarbiyah and TeacherTraining Faculty of UIN Alauddin Makassar. This research is a type of qualitative descriptiveresearch using a pedagogic and sociological approach. The research was conducted at the Facultyof Tarbiyah and Teacher Training at UIN Alauddin Makassar with the research subject being tenstudents of PGMI B class of 2017. The data collection method used in this study is by conductingobservations, interviews, and documentation. The results showed that the forms of learningdifficulties experienced by PGMI B students class 2017 Faculty of Tarbiyah and TeacherTraining UIN Alauddin Makassar in PAI Learning courses were difficulties in understandingPAI learning materials, difficulties in remembering the material being taught and the learningmethods used were monotonous. There are two factors that cause learning difficulties, namelyinternal and external factors. Internal factors consist of disturbed health conditions or physicaldisorders, low interest in learning, and lack of motivation to learn, while external factors forstudents are influenced by the learning environment at the university, the learning methods usedare less varied, and the conditions of the study rooms are not comfortable.